Boundary layer and flow control : its principles and application. - Lachmann, Gustav Victor, 1896- (Pergamon Press, 1961)
Boundary Layer and Flow Control: Its Principles and Application, Volume 2 focuses on the layer of fluid in the immediate area of a bounding surface where the effects of viscosity are substantial. This book is organized into two main topics--boundary layer control for low drag, and shock-induced separation and its prevention by design and boundary layer control. It specifically discusses the nature of transition, effect of two-dimensional and isolated roughness on laminar flow, and progress in the design of low drag aerofoils. The onset of separation effects for aerofoils and wings, shock-induced separation for laminar boundary layers, and shock-induced separation for laminar boundary layers are also deliberated. This volume is recommended to physicists and specialists interested in boundary layer and flow control.